Wavelet Fuzzy Brain Emotional Learning Control System Design for MIMO Uncertain Nonlinear Systems - Zhao, Jing; Lin, Chih-Min; Chao, Fei (Frontiers in Neuroscience, 2019)
This paper aims to present a novel efficient algorithm for the control of multiple input and multiple output (MIMO) uncertain nonlinear systems. A wavelet fuzzy brain emotional learning control (WFBELC) model is presented. This model comprises the benefit of wavelet function, fuzzy theory and brain emotional neural network. As a result, the approximation ability, the learning performance and the convergence rate will be effectively improved. The gradient descent method is used to adjust the parameters online of WFBELC and the Lyapunov function is employed to guarantee the convergence of the control systems. Two examples of uncertain nonlinear systems, a Duffing-Holmes chaotic system and a Chua’s chaotic circuit are studied to verify that the proposed model can be used to obtain the satisfactory control performance. Comparisons with other models show that the proposed WFBELC can be more suitable to deal with the influence of the uncertainty of the uncertain MIMO systems.